The Relationship Between Disease Severity and Hematologic Parameters in Geriatric Patients with Acute Pancreatitis - Onalan, Erhan; Gökalp, Yusuf; Yakar, Burkay (Progress in Nutrition, 2020)
Background: Acute pancreatitis (AP) is an emergency disease within the field of internal diseases. Itsprevalence in the older population has been increasing in parallel to the increase in the older population. Objectives: This study aims to demonstrate the relationship of the platelet/lymphocyte ratio (PLR) and the neutrophil/ lymphocyte ratio (NLR), which were shown to be markers related to systemic inflammation, with Ranson criteria, which indicate the severity of acute pancreatitis at the time of admission, in geriatric (65 years and above) and non-geriatric (age